Benchmark experiments for higher-order and full-Stokes ice sheet models (ISMIP–HOM) - Pattyn, Frank; Perichon, Laura; Aschwanden, A.; Breuer, B.; de Smedt, B.; Gagliardini, O.; Gudmundsson, Hilmar; Hindmarsh, Richard; Hubbard, Alun; Johnson, J. V.; Kleiner, Thomas; Konovalov, Y.; et al. (The Cryosphere, 2008)
We present the results of the first ice sheet model intercomparison project for higher-order and full-Stokes ice sheet models. These models are compared and verified in a series of six experiments of which one has an analytical solution obtained from a perturbation analysis. The experiments are applied to both 2-D and 3-D geometries; five experiments are steady-state diagnostic, and one has a time-dependent prognostic solution. All participating models give results that are in close agreement. A clear distinction can be made between higher-order models and those that solve the full system of equations. The full-Stokes models show a much smaller spread, hence are in better agreement with one another and with the analytical solution.